Cultural Mapping and Urban Regeneration: Analyzing Emergent Narratives about Bilbao - Ortega Nuere, Cristina; Bayón, Fernando (Culture and Local Governance / Culture et gouvernance locale)

(untitled) (Centre d'étude en gouvernance, Université d'Ottawa, 2015)
The role of culture in urban regeneration should be studied at different levels. Cultural mapping gives us a new understanding of the historical processes that have transformed public spaces in cities whose productive models and social relationships have undergone critical changes, affecting how they project their identity inside and outside their boundaries. Our research focuses on the case study of Bilbao (Basque Country, Spain). The first part of the analysis centres on a critical interpretation of the importance granted to cultural infrastructures in areas that were most intensely exposed to the changes which are known as the ‘Guggenheim effect’ on the international scene. This study especially examines the tension between today’s transformations and managing memories from the past. The second part analyses cultural mapping practices developed in emerging areas of the city such as the Zorrotzaurre peninsula, which is the new focus of the metropolitan development scheme. The proposals chosen for this study foster democratic responsibility in city management by using new technologies. They enable us take a closer look at some of the city’s most innovative collaborative cultural mapping practices, methodology and processes, as well as the theoretical frameworks that inspired them. Lastly, a proposal is put forth to implement participatory cultural mapping to identify the spillover effects of the cultural and creative industries located in renewed urban spaces.